Effect of deferiprone, an oral iron chelator, in diabetic and non-diabetic glomerular disease. (January 2013) - Rajapurkar, Mohan M.; Hegde, Umapati; Bhattacharya, Amalkumar; Alam, Muhammad G.; Shah, Sudhir V.
<x xml:space="preserve">Abstract</x> Compelling experimental evidence exists for the role of oxidants and iron in glomerular disease. In preliminary studies, we confirmed increased urinary catalytic iron in patients with glomerulonephritis and diabetic nephropathy. We conducted two separate single-center, prospective, single-armed, open-labeled, proof-of-concept studies to evaluate the safety and efficacy of an oral iron chelator in patients with glomerulonephritis and diabetic nephropathy. Study 1 comprised 15 patients with biopsy-proven glomerulonephritis who had persistent proteinuria despite treatment with steroids and/or cyclophosphamides. Study 2 comprised 38 adult patients with diabetic nephropathy. Patients in Study 1 were treated with deferiprone (50 mg/kg/day) in three divided doses for 6 months and Study 2 patients were treated for 9 months. In Study 1, two patients had severe gastrointestinal intolerance and withdrew from the study after one dose and are not included in the results. There was a significant reduction (47 ± 9% mean) in 24-h urinary protein (4.01 ± 1.61 to 2.21 ± 1.62 [p = 0.009]), with no significant changes in serum creatinine. In Study 2, treatment with deferiprone resulted in a marked, persistent drop in the mean albumin/creatinine ratio (187 ± 47 at baseline to 25 ± 7 mg/g, [p = 0.01]) and stable renal function over a 9-month period. No clinically significant adverse events were observed in either study. Although these are small, open-labeled, and non-randomized studies, our results suggest that future randomized, double-blind trials examining the utility of deferiprone to treat glomerular diseases appear warranted.